Influence Characteristics Of The Audit Committee, Work Stress, Turn The External Auditor And Cost Audit Of The Quality Of Audit Company Manufacturing Contained In Indonesia Stock Exchange - Fitria Nurandita (Institute of Computer Science (IOCS), 2021)
This study aimed to analyze the influence of gender, age, time of audit, the change of auditor and the external costs of the audit to the quality of auditors. Some previous studies of the quality of auditors showed different results - different. Therefore, other studies need to be done to test the theory about the quality auditor. The population of this study were 143 manufacturing companies. The sampling method used is purposive sampling method, in order to obtain a sample of 17 companies for 3 years of observation (2013-2015) with 51 observations (observation). Data were obtained from a sample of companies that are downloaded from the Indonesia Stock Exchange website. Data analysis technique used is descriptive statistical analysis and logistic regression analysis. The process of data analysis done first is descriptive analysis, logistic regression analysis and then test the hypothesis. The results of this study indicate that the partial replacement of external auditors and audit baiaya significantly affect the quality of auditors. As for gender, age and time has no effect partial audit of the Quality auditor. The results of this study simultaneously gender, age, time of audit, the change of the external auditor and audit fees simultaneous effect on audit quality.